Definition and conceptual model of genetics literacy: a systematic literature review - Hidayati Maghfiroh; Siti Zubaidah; Susriyati Mahanal; Hendra Susanto (International Journal of Public Health Science (IJPHS), 2023)
Genetic literacy is essential for promoting health and well-being in modern society. Although its importance is increasingly recognised, the definition and crucial dimension to construct a conceptual model are unclear, limiting the possibilities for measurement and comparison intervention. The study aims to review definitions and the conceptual models of genetics literacy and develop a new comprehensive definition and conceptual model based on the discovered dimensions that are relevant in the post-genomic era. We performed a systematic literature review using the Crossref, PubMed, and Scopus databases with Publish or Perish software. An automated content analysis was conducted to identify and develop conceptual model genetics literacy using NVivo 12 software. The review resulted in 10 definitions and 12 conceptual models. Automated content analysis showed that genetic literacy is defined as the ability of an individual to comprehend, use, correlate, assess, and propose genetic information to make arguments, reason, and decide on genetic issues in maintaining or improving the quality of personal and social well-being. Genetic literacy was conceptualised as a set of knowledge, a set of skills or interconnected. The conceptual model of genetics literacy covers two dimensions. i) Knowledge dimension: conceptual (nature of genetic material, transmission, genetic expression, genetic regulation, genetic determinism, genetic technology); sociocultural; epistemic. ii) Skills dimension: argumentation, informal reasoning, and decision-making skills. This definition and conceptual model can serve as a basis for developing interventions and measurements to support regulating, preventing, as well as promoting health and well-being.